Perceptions of the Implementation of Talent Management and Workforce Agility with Employee Engagement as a Mediating Variable in Employees - Tantri, Krisnia Ken; Matulessy, Andik; Rini, Rr. Amanda Pasca (Sinergi International Journal of Psychology, 2025)
The rapid advancement of digital technology and the dynamic VUCA environment require state-owned enterprises such as PT PLN (Persero) to continuously adapt through effective human resource strategies. This study aims to examine the relationship between perceptions of Talent Management implementation and Workforce Agility, with Employee Engagement as a mediating variable, among employees of PT PLN (Persero) East Java and Bali Main Transmission Unit Headquarters. Utilizing a quantitative approach, data were collected from 125 employees using validated perception scales and analyzed with regression and mediation tests. The findings indicate that Employee Engagement significantly mediates the relationship between perceptions of Talent Management and Workforce Agility, and that both Talent Management and Employee Engagement independently have a positive effect on Workforce Agility. These results suggest that integrated Talent Management and Employee Engagement initiatives are crucial in fostering agile and adaptive workforces, enabling organizations to respond effectively to industry transformations. The study recommends that PT PLN (Persero) and similar organizations prioritize strategic talent development and employee engagement to sustain competitiveness in an increasingly dynamic business landscape.